KEBUTUHAN RUANG TERBUKA HIJAU PUBLIK DI KABUPATEN TABALONG BERDASARKAN LUAS WILAYAH, JUMLAH PENDUDUK DAN KEBUTUHAN OKSIGEN - Rismauly Paskayanti; Kissinger Kissinger; Noor Arida Fauzana; Hilda Susanti (Universitas Lambung Mangkurat, 2022)
This study aims to assess the the need of green open space based on area, population, and oxygen needs in Tabalong regency, and aims to assess the direction of public green open space development of green open space needs in Tabalong regency. This research was conducted in Tabalong regency, South Kalimantan. This study used a quantitative method which emphasize to green open space data analyze based on area, population, and oxygen needs. The result showed that the need for Green Open Space in Tabalong based on area is 71.067 ha, based on population is 510,18 ha, and based on oxygen needs is 20.381 ha. Public Green Open Space Needs in Tabalong Regency based on area, population, and oxygen needs is still unfullfiled. Therefore the approach of Green Open Space development should be refers to Green Base Coefficent (KDH), conversion of non-productive open space to public green open space, and reforestation.